The Effects of the Amount of Black Sesame on Quality of Singapore Cendol with black Sesame seeds in Skimmed Milk - Chumkaew, Krittin (Science Essence Journal, 2019)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาพัฒนาสูตรลอดช่องสิงคโปร์เสริมงาดำนมสดขาดมันเนย โดยทำการศึกษาอัตราส่วนที่เหมาะสมของงาดำในเส้นลอดช่องสิงคโปร์ จำนวน 3 สูตร คือ ร้อยละ 2, 4 และ 6 โดยน้ำหนักของส่วนผสมทั้งหมด จากนั้นนำมาศึกษาคุณภาพทางกายภาพ ได้แก่ ค่าเนื้อสัมผัส ค่าสี คุณภาพทางประสาทสัมผัส และคุณค่าทางโภชนาการ ได้แก่ ปริมาณแคลเซียม และคุณค่าทางโภชนาการ ผลการศึกษา พบว่า ค่าเนื้อสัมผัส Springiness, Adhesiveness และค่าสี L* a* มีค่าลดลงอย่างมีนัยสำคัญทางสถิติ (p≤0.05) เมื่อเพิ่มปริมาณงาดำ จากการศึกษาคุณภาพทางประสาทสัมผัส พบว่า ลอดช่องสิงคโปร์เสริมงาดำร้อยละ 6 ได้รับการยอมรับทางประสาทสัมผัสมากที่สุด การศึกษาเปรียบเทียบปริมาณแคลเซียม พบว่า เส้นลอดช่องสิงคโปร์เสริมงาดำร้อยละ 6 มีปริมาณแคลเซียมสูงกว่าเส้นลอดช่องสิงคโปร์ ที่ไม่เสริมงาดำอย่างมีนัยสำคัญทางสถิติ (p≤0.05) และคุณค่าทางโภชนาการ ได้แก่ ไขมัน คาร์โบไฮเดรตทั้งหมด พลังงานทั้งหมดต่อ 100 กรัม และพลังงานจากไขมันต่อ 100 กรัม ของลอดช่องสิงคโปร์เสริม งาดำในนมสดขาดมันเนยทดแทนน้ำกะทิ มีปริมาณน้อยกว่าลอดช่องสิงคโปร์ที่ไม่เสริมงาดำและไม่ทดแทนด้วยนมสดขาดมันเนยอย่างมีนัยสำคัญทางสถิติ (p≤0.05) การศึกษาการยอมรับของผู้บริโภค พบว่า ผู้บริโภคยอมรับผลิตภัณฑ์โดยเฉลี่ยอยู่ในระดับการยอมรับมาก คำสำคัญ: ลอดช่องสิงคโปร์ งาดำ นมสดขาดมันเนย คุณภาพทางกายภาพ คุณค่าทางโภชนาการ ABSTRACT The objective of this study was to develop a recipe of Singapore Cendol with black sesame seeds in skimmed milk. The study analyzed three different recipes, namely 2%, 4% and 6% w/w of black sesame seeds in Singapore Cendol noodles and identified the most suitable recipe. There was physical property analysis covering texture analysis, color analysis, sensory evaluation and nutritional value analysis such as calcium analysis and other nutritional values. In addition, consumer acceptance of the product was also analysis. The results showed that in terms of texture analysis, springiness and adhesiveness as well as color values of L* and a* reduced statistically (p≤0.05). When there was more addition of black sesame seeds the 6% black sesame seed noodles were the highest acceptance in terms of sensory evaluation. Regarding calcium analysis, the 6% black sesame seed noodles provided higher level of calcium than the traditional Singapore Cendol noodles without black sesame seeds with a statistically significant difference (p≤0.05). Concerning nutritional values, the Singapore Cendol with black sesame seeds in skimmed milk provided less fat, carbohydrates, total energy per 100 g and total energy from 100 g of fat when compared to the traditional Singapore Cendol without black sesame seeds and skimmed milk with a statistically significant difference (p≤0.05). Regarding consumer acceptance, the consumers were satisfied with the product in all aspects in a high acceptance level. Keywords: Singapore Cendol, black sesame seeds, skimmed milk, physical properties, nutritional values Keywords: Singapore Cendol, black sesame seeds, skimmed milk, physical properties, nutritional values